"Community health workers bring value and deserve to be valued too:" Key considerations in improving CHW career advancement opportunities - Julie Smithwick; Jenesha Nance; Sarah Covington-Kolb; Ashley Rodriguez; Mike Young (Frontiers Media S.A., 2023)
IntroductionCommunity health workers (CHWs) are critical members of the public health workforce, who connect the individuals they serve with resources, advocate for communities facing health and racial inequities, and improve the quality of healthcare. However, there are typically limited professional and career building pathways for CHWs, which contribute to low wages and lack of career advancement, further resulting in turnover, attrition, and workforce instability.MethodsThe Center for Community Health Alignment (CCHA), within the Arnold School of Public Health at the University of South Carolina, utilized a mixed-method data collection strategy to provide a more in-depth understanding of this issue and ways that employers, advocates, and CHWs can address it.ResultsThemes across data sources emphasized the importance of retaining skilled and experienced CHWs and educating other health professions about CHWs' critical roles, and reported that doing so will result in decreased attrition professional growth, and improved program quality. CHWs and allies concluded that higher wages, valuing lived experience over formal education, and participation in additional training opportunities should be the primary factors considered for career advancement.DiscussionUtilizing input from experienced CHWs and CHW allies nationally, this article describes the importance of supporting CHW career advancement, shares best practices, and suggestions for designing strategies that organizations/employers can use to improve CHW career pathways to better support the CHW workforce and reduce attrition.